Optimal Reactive Power Dispatch using Improved Differential Evolution Algorithm - Hamid Falaghi; Arsalan Najafi (Majlesi Journal of Electrical Engineering, 2024)
Reactive power dispatch plays a key role in secure and economic operation of power systems. Optimal reactive power dispatch (ORPD) is a non-linear optimization problem which includes both continues and discrete variables. Due to complex characteristics, heuristic and evolutionary based optimization approaches have became effective tools to solve the ORPD problem. In this paper a new optimization approach based on improved differential evolution (IDE) has been proposed to solve the ORPD problem. IDE is an improved version of differential evolution optimization algorithm in which new solutions are produced in respect to global best solution. In the proposed approach, IDE determines the optimal combination of control variables including generator voltages, transformer taps and setting of VAR compensation devices to obtain minimum real power losses. In order to demonstrate the applicability and efficiency of the proposed IDE based approach, it has been tested on the IEEE 14 and 57-bus test systems and obtained results are compared with those obtained using other existing methods. Simulation results show that the proposed approach is superior to the other existing methods.Ø§ÙØ£ÙØ«Ù ÙÙØ© Ø±Ø¯ Ø§ÙÙØ¹Ù DISPATCH Ø¹Ù Ø·Ø±ÛÙ ØªØØ³Ù Ø§ÙØªÙØ§Ø¶ÙÛØ© ØªØ·ÙØ± Ø§ÙØ®ÙØ§Ø±Ø²ÙÛØ©Ø±Ø¯ Ø§ÙÙØ¹Ù Ø§Ø±Ø³Ø§Ù ÙÙØ© ÛÙØ¹Ø¨ Ø¯ÙØ±Ø§ Ø±Ø¦ÛØ³ÛØ§ ÙÛ Ø¹ÙÙÛØ© Ø¢ÙÙØ© ÙØ§ÙØ§ÙØªØµØ§Ø¯ÛØ© ÙØ£ÙØ¸ÙØ© Ø§ÙØ·Ø§ÙØ©. Ø§ÙØ£ÙØ«Ù Ø¹ÙÙ Ø±Ø¯ Ø§ÙÙØ¹Ù Ø§Ø±Ø³Ø§Ù ÙÙØ© (ORPD) ÙÙ Ø§ÙØÙ Ø§ÙØ£ÙØ«Ù ÙØºÛØ± Ø§ÙØ®Ø·Û Ø§ÙØ°Û ÛØ´ÙÙ Ú©ÙØ§ ÙÙ ØªÙØ§ØµÙ ÙØ§ÙÙØªØºÛØ±Ø§Øª Ø§ÙÙÙÙØµÙØ©. ÙØ¸Ø±Ø§ ÙØ®ØµØ§Ø¦Øµ ÙØ¹ÙØ¯Ø©Ø ÙØ£ØµØ¨Ø Ø§ÙÙÙØ¬ Ø§ÙØ£ÙØ«Ù Ø§ÙÚ©Ø´Ù Ø¹Ù ÙØ¬Ø±ÛØ§Øª Ø§ÙØ£ÙÙØ± ÙØ§ÙØªØ·ÙØ± Ø¹ÙÙ Ø£Ø³Ø§Ø³ Ø£Ø¯ÙØ§Øª ÙØ¹Ø§ÙØ© ÙØÙ ÙØ´Ú©ÙØ© ORPD. ÙÛ ÙØ°Ù Ø§ÙÙØ±ÙØ© ØªÙ Ø§ÙØªØ±Ø§Ø ÙÙØ¬ Ø§ÙØªØØ³ÛÙ Ø¬Ø¯ÛØ¯ ÛÙÙÙ Ø¹ÙÙ ØªØØ³ÛÙ ØªØ·ÙØ± Ø§ÙØªÙØ§Ø¶ÙÛØ© (IDE) Ø¹ÙÙ ØÙ ÙØ´Ú©ÙØ© ORPD. IDE ÙÙ ÙØ³Ø®Ø© ÙØØ³ÙØ© ÙÙ Ø§ÙØªÙØ§Ø¶ÙÛØ© Ø®ÙØ§Ø±Ø²ÙÛØ© Ø§ÙØªØ·ÙØ± Ø§ÙØ£ÙØ«Ù Ø§ÙØ°Û ÛØªÙ Ø¥ÙØªØ§Ø¬ ØÙÙÙ Ø¬Ø¯ÛØ¯Ø© ÙÛÙØ§ ÛØªØ¹ÙÙ Ø£ÙØ¶Ù ØÙ Ø¹Ø§ÙÙÛ. ÙÛ Ø§ÙÙÙØ¬ Ø§ÙÙÙØªØ±ØØ ÛØØ¯Ø¯ IDE Ø§ÙØ¬ÙØ¹ Ø§ÙØ£ÙØ«Ù ÙÙÙØªØºÛØ±Ø§Øª Ø¨ÙØ§ ÙÛ Ø°ÙÚ© ÙØ±Ø§ÙØ¨Ø© Ø§ÙÙÙÙØªÛØ© ÙÙÙØ¯ ÙØ§ÙØµÙØ§Ø¨ÛØ± Ø§ÙÙØÙÙØ§Øª ÙÙØ¶Ø¹ Ø£Ø¬ÙØ²Ø© ØªØ¹ÙÛØ¶ VAR ÙÙØØµÙÙ Ø¹ÙÙ Ø§ÙØØ¯ Ø§ÙØ£Ø¯ÙÙ ÙÙ Ø§ÙØ®Ø³Ø§Ø¦Ø± Ø§ÙØ³ÙØ·Ø© Ø§ÙØÙÛÙÛØ©. ÙÙ Ø£Ø¬Ù Ø¥Ø«Ø¨Ø§Øª Ø¥ÙÚ©Ø§ÙÛØ© ØªØ·Ø¨ÛÙ ÙÚ©ÙØ§Ø¡Ø© ÙÙØ¬ IDE Ø¹ÙÙ Ø£Ø³Ø§Ø³ Ø§ÙÙÙØªØ±ØØ ÙÙØ¯ ØªÙ Ø§Ø®ØªØ¨Ø§Ø±Ù Ø¹ÙÙ Ø£ÙØ¸ÙØ© Ø§Ø®ØªØ¨Ø§Ø± IEEE 14 Ù 57 Ø¨Ø§Øµ ÙØØµÙ ØªØªÙ ÙÙØ§Ø±ÙØ© Ø§ÙÙØªØ§Ø¦Ø¬ ÙØ¹ ØªÙÚ© Ø§ÙØªÛ ØªÙ Ø§ÙØØµÙÙ Ø¹ÙÛÙØ§ Ø¨Ø§Ø³ØªØ®Ø¯Ø§Ù Ø·Ø±Ù Ø£Ø®Ø±Ù ÙÙØ¬ÙØ¯Ø©. ÙØªØ¨ÛÙ ÙØªØ§Ø¦Ø¬ Ø§ÙÙØØ§Ú©Ø§Ø© Ø£Ù Ø§ÙÙÙØ¬ Ø§ÙÙÙØªØ±Ø ÙØªÙÙÙØ© Ø¹ÙÙ Ø§ÙØ·Ø±Ù Ø§ÙØ£Ø®Ø±Ù Ø§ÙÙØ§Ø¦ÙØ©.